Activation of endogenous retroviruses during brain development causes an inflammatory response. (1st March 2021) - Jönsson, Marie E; Garza, Raquel; Sharma, Yogita; Petri, Rebecca; Södersten, Erik; Johansson, Jenny G; Johansson, Pia A; Atacho, Diahann AM; Pircs, Karolina; Madsen, Sofia; Yudovich, David; Ramakrishnan, Ramprasad; et al.
Abstract: Endogenous retroviruses (ERVs) make up a large fraction of mammalian genomes and are thought to contribute to human disease, including brain disorders. In the brain, aberrant activation of ERVs is a potential trigger for an inflammatory response, but mechanistic insight into this phenomenon remains lacking. Using CRISPR/Cas9‐based gene disruption of the epigenetic co‐repressor protein Trim28, we found a dynamic H3K9me3‐dependent regulation of ERVs in proliferating neural progenitor cells (NPCs), but not in adult neurons. In vivo deletion of Trim28 in cortical NPCs during mouse brain development resulted in viable offspring expressing high levels of ERVs in excitatory neurons in the adult brain. Neuronal ERV expression was linked to activated microglia and the presence of ERV‐derived proteins in aggregate‐like structures. This study demonstrates that brain development is a critical period for the silencing of ERVs and provides causal in vivo evidence demonstrating that transcriptional activation of ERV in neurons results in an inflammatory response. SYNOPSIS: Developmental silencing of ERVs is crucial for their maintained repression in the adult brain. Disrupted ERV silencing resulted in both cell‐intrinsic and cell‐extrinsic effects as well as an inflammatory response. CRISPR‐based deletion of the epigenetic co‐repressor protein Trim28 in neural progenitor cells results in upregulation of a large number of ERVs. Neuronal Trim28 CRISPR‐KO in the adult brain had no effect on ERV expression. Cre‐induced loss of Trim28 in neural cells during brain development resulted in ERV expression in the adult brain. Dysregulation of ERVs in neural cells of the adult brain results in an inflammatory response. Abstract : Deletion of epigenetic co‐repressor Trim28 aberrantly upregulates endogenous retroviruses (ERV), resulting in microglia activation and the expression of ERV‐derived proteins in adult mouse brains.